Extracellular vesicles released by microglia and macrophages carry endocannabinoids which foster oligodendrocyte differentiation - Lombardi, Marta; Scaroni, Federica; Gabrielli, Martina; Raffaele, Stefano; Bonfanti, Elisabetta; Filipello, Fabia; Giussani, Paola; Picciolini, Silvia; de Rosbo, Nicole Kerlero; Uccelli, Antonio; Golia, Maria Teresa; D’Arrigo, Giulia; et al. (Frontiers in Immunology, 2024)
Microglia and macrophages can influence the evolution of myelin lesions through the production of extracellular vesicles (EVs). While microglial EVs promote in vitro differentiation of oligodendrocyte precursor cells (OPCs), whether EVs derived from macrophages aid or limit OPC maturation is unknown. Here we show that macrophage-derived EVs do not promote OPC differentiation, and those released from macrophages polarized towards an inflammatory state inhibit OPC maturation. However, their lipid cargo promotes OPC maturation in a similar manner to microglial EVs. Raman spectroscopy and liquid chromatography-mass spectrometry identify the promyelinating endocannabinoids anandamide and 2-arachidonoylglycerol in EVs released by both macrophages and microglia in vitro and circulating in human plasma. Analysis of OPC differentiation in the presence of the endocannabinoid receptor antagonists SR141716A and AM630 reveals a key role of vesicular endocannabinoids in OPC maturation. From this study, EV-associated endocannabinoids emerge as important mediators in microglia/macrophage-oligodendrocyte crosstalk, which may be exploited to enhance myelin repair.